54 Interferon-α reduces early atherosclerosis in patients with Behcet's Syndrome. Issue 20 (23rd September 2011) - Chan, C F; Keenan, N G; Lightman, S; Haskard, D O; Pennell, D J
Abstract : Introduction: Interferon-α is an immunoregulatory cytokine with several biological functions that may influence atherosclerosis. We took the opportunity to analyse atherosclerosis-related outcomes in patients entering a randomised controlled clinical trial testing the effect of interferon-α on Behcet's Syndrome. Methodology: 30 patients with Behcet's Syndrome were studied with MRI at 0, 6 and 12 months after randomisation to interferon-α treatment (n=14) or standard therapy (n=16), measuring carotid wall volume, brachial artery flow-mediated reactivity and cardiac function. Serum antibodies to phosphorylcholine (PC) were measured by ELISAs. Results: We found no significant differences in baseline cardiovascular risk factors (eg, smoking, BP and lipids) between the groups. Over 12 months, the interferon-α treated group showed a significant reduction in the carotid arterial wall volume between the groups (701.0 mm 3 vs 690.1 mm 3, p<0.005) and, a significant treatment effect change of 4.4% in endothelial-dependent flow-mediated dilatation (p<0.01). We also found a significant increase in IgM auto-antibodies directed against PC (0.7±0.4 vs 0.8±0.4, p=0.04). There was no significant difference in the other measured cardiac parameters or antibody estimations. Conclusion: This is the first clinical study to test the effects of interferon-α on atherosclerosis, and maybe the first to test the effects of any cytokine. Reduction in carotid wall volume maybe related to stimulation of homeostatic IgM antibodies with improved clearance of biologically active oxidatively-modified lipids and reduction in endothelial dysfunction. It remains to be determined whether interferon-α has the same effects in otherwise healthy, non-Behcet's Syndrome individuals.